Cultural adaptation of ENABLE (Educate, Nurture, Advise, Before Life Ends) an early palliative care model for Iranian patients with heart failure and their caregivers: a qualitative study protocol - Arvin Mirshahi; Ali Khanipour-Kencha; Marie Bakitas; J. Nicholas Odom; Rachel Wells; Arpi Manookian (Archives of Public Health)
Abstract Background ENABLE (Educate, Nurture, Advise, Before Life Ends) is a model of nurse-led, early palliative care that was originally developed for U.S. patients with advanced cancer and their family caregivers and then adapted for patients with heart failure. ENABLE coaching topics include problem-solving, communication, advance care planning, symptom management, and self-care. The purpose of this paper is to detail a qualitative study protocol to assess the cultural acceptability of ENABLE among heart failure patients and their family caregivers in Iran. Methods This qualitative study employs reflexive thematic analysis (RTA) to guide the cultural adaptation of the ENABLE model. The study is conducted in two phases. In Phase 1, the ENABLE content will be translated and validated into Persian using a forward-backward translation process and expert panel review to ensure linguistic and cultural appropriateness. In Phase 2, semi-structured interviews will be conducted with individuals living with HF, their caregivers, and healthcare providers at Tehran University of Medical Sciences. The one-on-one semi-structured interviews will explore three main areas: (1) the primary needs and challenges faced by individuals with heart failure and their family caregivers, (2) the extent of patients’ involvement in healthcare decision-making, and (3) participants’ preferences for content and delivery method of ENABLE. Maximum variation sampling will be employed to ensure diverse representation, and data collection will continue until saturation is achieved. Interview audio recordings will be transcribed verbatim and analyzed using Braun and Clarke's reflexive thematic analysis approach. The analysis will involve iterative coding to identify patterns and the development of themes that align with the core components of the ENABLE model while ensuring cultural relevance. Trustworthiness and rigor will be ensured through reflexivity, peer debriefing, and data triangulation, ensuring credible and robust findings to guide the cultural adaptation of the ENABLE model for Iran. Discussion This study will develop a framework for adapting the ENABLE model to Iran, offering insights into cultural and contextual factors influencing palliative care. The adapted model aims to enhance the quality of life for individuals with HF and their caregivers while addressing gaps in palliative care delivery in Iran.